PROFIL TINGKAT KEBUGARAN ANAK USIA 5-14 TAHUN KOTA ADMINISTRATIF JAKARTA TIMUR - Fajar Vidya Hartono (Jurnal Ilmiah Visi, 2014)
Children aged 5 â€“ 14 years Fitness level profile in Jakarta Timur, this research aims to determine the extent to which fitness level children age range 5 till 14 years old in Jakarta Timur. This research using a test and non test techniques with the survey method. A collection for the sample using a proportionate stratified random sampling techniques. As many as 121 children as sample. Tested using a MFT (Multistage Fitness Test) The multi-stage fitness test, also known as the bleep test, beep test, pacer test, Leger-test or 20-m shuttle run test, is a series of stages that have different tasks sometimes used by sports coaches and trainers to estimate an athleteâ€™s VO2 max(maximum oxygen uptake). The pacer test is â€œprogressive aerobic cardiovascular endurance testâ€. The test is especially useful for players of sports such as rugby, football, Australian rules football, Gaelic football, hurling, hockey, netball, handball,tennis, squash, and fitness testing in schools and colleges plus many other sports; employed by many international sporting teams as an accurate test of cardiovascular fitness, one of the more important components of Fitness. The existing data then processed and analyzed with a statistic deskriptif techniques. From measurements made it can be concluded that in general a children fitness level has a high point category, the district who has a high fitness level points in sub-district Makasar with ratio 31.98 points, and a lowest fitness level points located in sub-district Duren Sawit with 22.42 level points ratio. The survey result revealed is physical fitness related to a good activity perform and it will to conduce a better fitness level. Level of fitness predispose a learning achievement and all of activities who nature playing and requires a lot of energy because a children growth aged 5 â€“ 14 years is phase of motor development and when directed with a better programe it will be a good potension in future.